Slowbalisation – Evidence of a Slowdown in Internationalisation - Pawel FOLFAS; Anna ODROBINA (Communications of International Proceedings, 2020)
In recent years, the term ‘slowbalisation’ has appeared in the economic literature, meaning changes in the global economy slowing down the process of the internationalisation of economic activity. These changes are characterised by a marked slowdown and even a regression of international economic relations. The article attempts to scrutinize the symptoms and characteristics of a new stage of globalisation. Based on analyses of international trade in goods, services, FDI and international production, it demonstrates that there are grounds for ‘slowbalisation’, especially in the context of observed geopolitical activities, with trade war being the most important of them, and technological progress focussed on digitisation, automation and artificial intelligence.
Keywords: Internationalisation; globalisation; international trade; global value chains (GVCs).